Analisis Respon IHSG Terhadap Surprise Variabel Makroekonomi Indonesia Dan Amerika Serikat Menggunakan Metode ARCH M Model - Sadewo, Ery (Jurnal Ilmiah Mahasiswa FEB, 2016)
This  paper  investigates  the  response  of  stock  market  price  to  macroeconomic  surprises.  Using Indonesia and US  data, we find that Indonesian stock price is influenced by domestic macroeconomic surprises. Indonesian stock price is also influenced by some us macroeconomic surprises namely output surprise, inflation surprise while us interest rate surprise does not influence Indonesian stock price. Moreover S&P index have positive effects to Indonesian stock Keywords: Stock price, Macroeconomic surprises